Diagnostic value of Doppler frequency spectrum analysis in the evaluation of stenotic carotid artery disease - Kataoka, Satoshi (Japanese Journal of Stroke, 1988)
In order to evaluate the usefulness of spectrum analysis for stenotic internal carotid artery disease, quantitative frequency spectrum analysis was used to study internal and common carotid artery disease from 22 control subjects-34 vessels and 31 patients-43 stenotic vessels which were diagnosed angiographically. Continuous wave directional Doppler ultrasound device and Doppler frequency spectrum analyzer were used for ultrasonic studies. Peak systolic frequency (PSF) and peak diastolic frequency (PDF) of carotid artery in normal subjects proved by angiography were constant along the vessel from common carotid to internal carotid artery at four points, and the values of PSF were between 1.4 and 4.4 KHz. The maximum PSF with stenotic internal carotid artery was regionally increased above 2.4 KHz and PSF ratio between internal carotid artery and common carotid artery (PSF-ratio (ICA/CCA)) was above 1.33. The sensitivity of PSF above 4.0 KHz for stenotic internal carotid artery disease was 72.1% and the specificity was 94.1%. The sensitivity of PSF-ratio (ICA/CCA) above 1.50 was 62.8% and its specificity was 82.3%. In the stenotic group, the % stenosis of internal carotid artery was correlated significantly (p<0.05-0.01) with PSF of stenotic portion and with PSF-ratio respectively. There is a positive linear correlation between the % stenosis of internal carotid artery (X) and PSF of stenotic portion (Y) and this is expressed as follows; Y=0.052X + 2.79, r=0.586, (p<0.001). And there is also a positive linear correlation between the % stenosis of internal carotid artery (X) and PSF-ratio (ICA/CCA) (Y) as follows; Y=0.025X + 1.11, r=0.503, (p<0.001) until about 80% stenosis. The localized elevation of PSF more than 4.0 KHz in internal carotid artery and PSF-ratio (ICA/CCA) more than 1.50 were found to have diagnostic value for stenotic cervical internal carotid artery disease. And PSF of internal carotid artery and PSF-ratio are quantitatively useful parameters for stenotic cervical internal carotid artery disease and these can be used for the detection of stenotic lesions in carotid artery disease clinically